The role of community health workers in influencing social connectedness using the household model: a qualitative case study from Malawi - Myness Kasanda Ndambo; Fabien Munyaneza; Moses Aron; Henry Makungwa; Basimenye Nhlema; Emilia Connolly (Taylor & Francis Group, 2022)
Background Community health workers (CHWs) play a vital role in facilitating social connectedness, building trust, decrease stigma, and link communities to essential healthcare and social support services. More studies are needed to understand the factors facilitating these interactions among CHWs, clients, and community members. Objective This study examined the CHW role and relationships between CHWs, communities, and health facilities that promote trust, positive relationships, and social connectedness. Methods In 2016, the CHW program in Neno District, Malawi, was transitioned to a household-level assignment of CHWs to provide screening, linkage to care, and psychosocial and chronic disease support from a disease-based program. We employed an exploratory qualitative study with thematic analysis linked to Fredrickson's broaden-and-build theory of positive emotions through focus group discussions (FGDs) and in-depth interviews (IDIs) to understand the impact of the household assignment. We purposively sampled community stakeholders, CHWs, health service providers, and clients (total N = 180) from October 2018 through March 2020. All interviews were audiotaped, transcribed verbatim, translated, coded, and analyzed. Results Participants reported decreased stigma and discrimination with increased trust and confidence in CHWs with household-level assignment. Positive relationships between CHWs in their households, community members, and health facility staff fostered health knowledge, individual agency, and personal resources for the community members to access health services. Community members' personal resources of increased health knowledge, trust, gratitude, and social support improved social connectedness and subjective wellbeing. Areas to improve positive relationships include CHWs maintaining confidentiality and caring for pregnant women. Conclusion Our study findings demonstrate that by building solid relationships as a community chosen, well informed, and household-level workforce, CHWs can develop positive relationships with communities and the health-care facility staff through building knowledge, trust, gratitude, and hope. Further work is needed in maintaining CHW confidentiality and new ways to approach culturally sensitive health areas.